ESTRUS INDUCTION, FERTILITY AND BIOCHEMICAL PROFILE IN TRUE ANESTRUS SURTI BUFFALO FOLLOWING DIFFERENT ESTRUS SYNCHRONIZATION PROTOCOLS - PATEL, AJ; PATEL, JA; DHAMI, AJ; PRAJAPATI, JP; PARMAR, SC (The Indian Journal of Animal Reproduction, 2022)
Under field conditions, postpartum (>90d) true anestrus Surti buffalo treated with four different hormonal protocols (n=11 each), viz., Doublesynch, Estradoublesynch, Triu-B/PRID, PRID+PMSG and untreated control revealed 81.8-100% estrus induction response. The respective conception rates obtained following AI at induced estrus was 27.3, 27.3, 18.2 and 45.4%, with an overall conception rate of three cycles as 63.6, 54.5, 63.6 and 81.8%, which was much higher than control buffalo (18.2%). Plasma cholesterol between conceived and nonconceived buffalo was different (p
Keywords: Buffalo; Estrus induction; Fertility; Plasma protein; Plasma cholesterol